ChemInform Abstract: Iodide‐Catalyzed Synthesis of Secondary Thiocarbamates from Isocyanides and Thiosulfonates. Issue 44 (13th October 2016) - Mampuys, Pieter; Zhu, Yanping; Sergeyev, Sergey; Ruijter, Eelco; Orru, Romano V. A.; Van Doorslaer, Sabine; Maes, Bert U. W.
Abstract: This novel facile synthesis of S‐alkyl and S‐aryl thiocarbamates proceeds under mild conditions and tolerates a wide range of functional groups.